2017
DOI: 10.1111/sdi.12652
|View full text |Cite
|
Sign up to set email alerts
|

The complex relationship among arteriovenous access, heart, and circulation

Abstract: There are currently near 400 000 patients on hemodialysis in the United States. More than 50% of those treated by chronic hemodialysis die because of a cardiovascular (CV) event. The majority of these patients have functional arteriovenous fistulas (AVFs).AVFs have an adverse effect on cardiac function, but their exact contribution to CV morbidity is not clear. It has long been known that a vascular access with an inappropriately high-flow rate may cause high-output heart failure. Paradoxically, there may be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…However, after the initial drop, SaO 2 and PaO 2 levels increased to slightly higher than baseline SaO 2 , both in this study and that of Meyring‐Wosten This may have been due to an improvement in fluid status resulting in less pulmonary congestion and a reduced A‐a oxygen gradient . Interestingly, regarding long‐term effects, the creation of an arteriovenous fistula may improve arterial oxygenation through cardio‐pulmonary recirculation, although to the best of our knowledge this effect has only been studied in patients with COPD, and not in renal patients …”
Section: Changes In Arterial Oxygen Saturation During Dialysismentioning
confidence: 56%
See 1 more Smart Citation
“…However, after the initial drop, SaO 2 and PaO 2 levels increased to slightly higher than baseline SaO 2 , both in this study and that of Meyring‐Wosten This may have been due to an improvement in fluid status resulting in less pulmonary congestion and a reduced A‐a oxygen gradient . Interestingly, regarding long‐term effects, the creation of an arteriovenous fistula may improve arterial oxygenation through cardio‐pulmonary recirculation, although to the best of our knowledge this effect has only been studied in patients with COPD, and not in renal patients …”
Section: Changes In Arterial Oxygen Saturation During Dialysismentioning
confidence: 56%
“…55 Interestingly, regarding long-term effects, the creation of an arteriovenous fistula may improve arterial oxygenation through cardio-pulmonary recirculation, although to the best of our knowledge this effect has only been studied in patients with COPD, and not in renal patients. 56,57 11 | POSSIBLE COMPLICATION S OF HYPOXEMIA Therefore, whereas the HD procedure appears to have bimodal effects on SaO 2 and the pathophysiological effects of the initial drop appears to have been elucidated, patient-related factors undoubtedly also play a major role in persistent hypoxemia during HD as outlined previously. The consequences of prolonged arterial hypoxemia remain unexamined.…”
Section: Saturation During Dialysismentioning
confidence: 94%
“…However, the preventive effect of flow reduction on heart failure has not yet been confirmed. 6 ) A prospective study has reported that flow volumes greater than 2 l/min were strongly correlated with the occurrence of high output heart failure. 8 ) Thus, according to the high predictive power of the study mentioned above, it is possible that flow reduction prevented potential heart failure in two of the three patients in our study who had a flow volume greater than 2 l/min.…”
Section: Discussionmentioning
confidence: 99%
“…High flow access (HFA) for hemodailysis can occasionally lead to disorders such as venous hypertension, 1 , 2 ) hemodialysis access-induced distal ischemia (HAIDI), 3 5 ) and high output heart failure 6 9 ) ; therefore, accurate diagnosis and appropriate treatment are essential to limit subsequent complications. 10 ) While radical treatment for HFA involves access closure, flow reduction procedures are used to preserve access.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter, observational cohort study in 602 participants identified AFV blood flow rate, diameter, and depth as moderate predictors of AVF maturation [21]. However, there are no generally agreed upon hemodynamic criteria for determining AVF maturity and cardiovascular adaptation to the AVF [22]. Additionally, there is no agreed upon process to follow fistula maturation and attempt cannulation based on prior hemodynamic information.…”
Section: Introductionmentioning
confidence: 99%